School education in Pakistan a sector assessment. (Country sector and thematic assessments.)
While average years of schooling in Pakistan have increased along with life expectancy and per capita income, inequality remains high and, by other education measures, the record remains dismal. Illiteracy is widespread and almost 23 million children aged 5-16 are not in school a worrying statistic for a country whose current workforce is young, mostly unskilled, and poorly prepared for productive employment.